Clinico-pathological features of oral squamous cell carcinoma and oral potentially malignant disorders: A comparative study from a tertiary care hospital of Karachi - Khan, Samreen; Muhammad Mohiuddin Alamgir; Uzma Bukhari; Muhammad Shuja Farrukh; Qurat-Ul-Ain; Areeba Shafiq (Journal of the Pakistan Medical Association, 2025)
Objectives: To compare the clinicopathological features of oral squamous cell carcinoma and oral potentially malignant disorders. Method: The analytical, cross-sectional study was conducted at the Dow University of Health Sciences, Karachi, from July 2022 to April 2023, and comprised cases of oral squamous cell carcinoma in group A and those of oral potentially malignant disorders in group B. Data, including detailed clinical history, radiological findings and histopathology reports, was collected using a predesigned questionnaire. Data was analysed using SPSS 21. Results: Of the 90 patients, 45(50%) were in group A; 34(75.6%) males and 11(24.4%) females with mean age 49.44±11.53 years. The remaining 45(50%) patients were in group B; 35(77.8%) males and 10(22.2%) females with mean age 50.82±13.34 years (p>0.05). The most common oral habit reported in both the groups was tobacco in smokeless form; 33(73.3%) in group A and 37(82.2%) in group B. The most reported site in group A was the buccal mucosa of the cheek 29(64.4%), followed by the tongue 14(31.1%). Most cases in group A were of moderately differentiated tumours 38(84%), and 21(46.7%) were in advanced stage IV at the time of presentation. Majority of the cases in group B showed mild dysplasia on histology 29(65%). Conclusions: There were no significant differences patients of oral squamous cell carcinoma and oral potentially malignant disorders except that oral cancer cases presented in the advanced stage at the time of diagnosis. Key Words: Clinicopathological features, Oral cancer, Oral squamous cell carcinoma, Oral epithelial dysplasia.